Diabetic pregnancy activates the innate immune response through TLR5 or TLR1/2 on neonatal monocyte. (September 2016) - Yanai, Sakika; Tokuhara, Daisuke; Tachibana, Daisuke; Saito, Mika; Sakashita, Yuko; Shintaku, Haruo; Koyama, Masayasu
Highlights: Maternal diabetes mellitus induces excessive inflammatory activation in neonatal monocytes via TLR5- or TLR1/2-mediated innate immune response. TLR5- and TLR1/2-mediated excessive production of IL-8 or TNF-α (or both) in the neonates of diabetic mothers may contribute to the deleterious outcome after early neonatal infection with E. coli or L. monocytogenes . Maternal obesity may contribute to the activation of neonatal innate immunity. Abstract: Diabetes mellitus (DM) during pregnancy causes congenital malformation, macrosomia, respiratory distress syndrome, and other abnormalities in neonates, but whether maternal DM affects the neonatal innate immune system is unknown. Therefore we aimed to reveal the influence of DM in pregnancy on the toll-like receptor (TLR)–mediated innate immune response in neonates. Cord blood was collected after full-term vaginal or cesarean delivery and classified into a DM group (n = 8) and non-DM (control) group (n = 7). Mononuclear cells were harvested from cord blood by using density gradient centrifugation, after which anti-CD14 magnetic beads were used to isolate monocytes from the mononuclear population. After monocytes were cultured with lipopolysaccharide (TLR4 ligand), flagellin (TLR5 ligand), Pam3CSK4 (TLR1/TLR2 ligand), zymosan (TLR2/TLR6 ligand), or macrophage-activating lipopeptide (TLR2/TLR6 ligand) for 12 h, the cytokine levels (interleukin [IL]-8, IL-6, IL-1β, IL-10, tumor necrosis factor alpha and IL-12) in the culture supernatants were measured. Compared with the control group, the DM group had higher concentrations of IL-8 ( P = 0.01) and tumor necrosis factor alpha ( P = 0.02) after monocyte cultures were stimulated with Pam3CSK4 and higher concentrations of IL-8 ( P = 0.01) after flagellin treatment. In contrast, stimulation with lipopolysaccharide, zymosan, or macrophage-activating lipopeptide did not lead to any difference in cytokine profiles between the two groups. These data indicate that maternal DM induces excessive inflammatory activation in neonates via a TLR5- or TLR1/2-mediated innate immune response.